571 The Influence of Climate on Critically Ill Pregnant COVID-19 Patients, as Revealed by the Inflammation Indexes, in Spring versus Autumn 2021 Infection (Balneo and PRM Research Journal, 2024)
(1) Background: COVID-19 infection can result in prolonged systemic inflammation in patients. We observed that there was increased inflammation and complement and antibody activities in severe versus non-severe forms of COVID-19 in pregnant patients. (2) Methods: In a retrospective study, we included all pregnant patients admitted to the Elena Doamna Obstetrics and Gynecology Hospital with a critical form of COVID-19 infection between 1 January and 1 December 2021. The blood counts collected on the specific A, H and E Brixia score- collection days, or the ones collected closest to those days, were considered in our study. We also studied the differences between the two groups regarding the inflammation indexes exhibited on those specific days: A (admittance), H (highest Brixia score), and E (end of hospitalization). (3) Results: The values of NLR, dNLR, SII, and AISI are significantly higher and IIC is significantly lower for the spring group (when the Alpha variant dominated in Romania) versus the autumn group (when the Delta variant dominated), especially on the H and E Brixia score-collection days. (4) Conclusions: These results suggest that severe-COVID-19 inflammation was significantly higher in the spring of 2021 in Romania than in autumn 2021, in regard to pregnant patients.